Thin Metal Film Sensors - C. R. Tellier (Active and Passive Electronic Components)
During the last decade some progress have been made in the field of sensors using thin film techniques. In particular thin metal film strain gauges and thin film temperature sensors based on the temperature dependent resistivity of metal are now commonly used. But changes in other transport parameters with various measurands are also useful for the design of metal film sensors. Difficulty arises in thin film techniques when structural defects are frozen in films.